Pembuatan Peta Batas Wilayah Kelurahan Pelabuhan Kecamatan Samarinda Kota - Andrew Stefano; Sri Endayani (Journal of Geomatics Engineering, Technology, and Science, 2023)
The practical science of Geodesy is making maps of large or small parts of the earth's surface. The City of Samarinda currently has the problem of not having a city map for city government officials or local residents. The absence of a city map makes it difficult for city officials and the public to find out information on sub-district boundaries and land use in the Pelabuhan Subdistrict area, the District of Samarinda Kota. To create a map of the boundaries of the Pelabuhan Subdistrict above, a survey was carried out using a handheld GPS to surround and identify the boundaries of the Pelabuhan Subdistrict according to the direction of one of the District of Samarinda Kota officials who was very knowledgeable about the conditions in the field. The creation of the Pelabuhan Subdistrict boundary map was carried out through a digitization process in the QGIS application by displaying corrected satellite imagery. Through the QGIS application, digitization is carried out according to the conditions and conditions at the location, by paying attention to the appearance of the earth on satellite images of the City of Samarinda. The objects digitized in this process are the boundaries of the Pelabuhan Subdistrict, the District of Samarinda Kota, and public facilities. Apart from that, interpretation was carried out and it was found that land use in the District of Samarinda Kota, the City of Samarinda includes green open space, city utilities and built-up land. Land use in the form of trade and service centers is almost evenly distributed throughout the District of Samarinda Kota.